RESPONSE TIME IN THE EMERGENCY ROOM IN A HOSPITAL - Muhammad Asepta Saputra; Guswari Dirga Santara; Keisha Rahma Juliani; Febi Sugiana (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
ABSTRACT: This scooping review maps the factors influencing response time in the emergency department (ED) and its impact on service quality. The majority of studies (2021–2025) indicate that response times meet the standard of ≤5 minutes. Response speed is influenced by internal factors within healthcare workers (stress, knowledge, experience, motivation) and external factors (visitor load, systems, facilities, disaster preparedness), with overload and overcrowding being the primary causes of delays. Optimal response times improve patient safety, service satisfaction, and reduce family anxiety, and are supported by the implementation of a five-level triage system. Background: Emergency Departments (EDs) play a crucial role in patient safety through rapid response time, a key indicator of service quality. A rapid response time contributes to successful emergency management, patient safety, and family satisfaction, while delays can worsen clinical conditions and increase the risk of mortality. Response speed is influenced by factors internal to healthcare personnel and external to the service system, including triage effectiveness and resource availability. However, studies on the impact of overload and overcrowding on response time, particularly in Indonesia, are still limited. Therefore, this scooping review aims to map scientific evidence related to the influence of overload and overcrowding on response time in the ED as a basis for improving service quality and safety. Methods: This study is a scooping review aimed at mapping scientific evidence related to response time in the emergency department (ED) and the factors influencing it, including patient overload and overcrowding. The review was conducted in 2025, analyzing articles published between 2021 and 2025 obtained from PubMed, ScienceDirect, and Google Scholar, following PRISMA guidelines. Of the 12,647 identified articles, 10 were selected that met the criteria for analysis. Data synthesis was performed by grouping themes of timeliness of service, internal and external factors, and their impact on service quality and patient safety in the ED. Results: This scooping review analyzed 10 selected articles, consisting of nine national and one international study, using observational, cross-sectional, correlational, and literature review designs. All studies discussed response time in the emergency department (ED), the factors influencing it, and its impact on service quality, patient safety, and patient and family satisfaction.Conclusion: Response time is a key indicator of emergency department (ED) service quality, directly impacting patient safety and family comfort. Response speed is influenced by both internal factors within healthcare workers and external factors such as patient load, infrastructure, and triage implementation. Achieving a standard response time of <5 minutes reflects the effectiveness of emergency department management, necessitating improvements in healthcare worker competency, optimization of the triage system, control of overcrowding, and ongoing monitoring of service quality.